Comportamento químico de azóis trialoacetil/trifluormetil substituídos em reações de alilação: síntese de álcoois trialometil heteroaril homoalílicos - Wiethan, Carson Wanderley (2013)
The present work reports the synthesis of homoallylic alcohols derived from trihaloacetyl/trifluormethyl substituted azoles employing a simple methodology, with excellent cost benefit and able to furnish the desired products with satisfactory yields. The synthetic approach involved the increase of the scope of a previous work of the research group NUQUIMHE, where three new pyrazoles containing a dimethyl acetal aldehyde function bonded to the carbon 3 of the heterocycle (5a-c) were synthetized from cyclocondensation reactions between methyl, phenyl and tert-butyl hydrazine and the 4,6,6-trimethoxy-1,1,1-trifluorohex-3-en-2-one (3f) in alcoholic medium. The compounds were obtained like oils, with yields in the range of 89 98 %. In a next step, was performed the deprotection of the acetal moiety of the pyrazoles (5a-c), in order to obtain the corresponding aldehydes (6a-c). To this, it was employed a solution of CHCl3 and aqueous trifluoroacetic acid under reflux for a reactional time of 4 hours. This methodology allowed isolating the desired products with yields in the range of 68 87 %. These compounds were employed to optimize the reactional conditions used in the synthesis of the homoallylic alcohols described in this dissertation. The allylation reaction of pyrazoles 6a-c was performed using allylaluminum reagents generated in situ from the catalytic insertion of aluminum to allyl bromides. The methodology was effective to synthetize the allylic alcohols 7a-c, which were obtained like oils, in the range of 84 90%. Of an analogue way, were realized the allylations of trihaloacetyl substituted 1,2,3-triazoles (4a-f). These precursors, obtained from 1,3 dipolar cycloadditions between the 2,6-difluorobenzyl azide (1) and trihalomethyl substituted enones (3a-f), were reacted with allylaluminum nucleophiles derived from allyl and crotyl bromides, furnishing the corresponding homoallylic alcohols with yields in the range of 85 94 %. In view of accessible price and exquisite chemical reactivity, the employed allylaluminum reagents proved to be an excellent choice for the allylations reactions of the azole 4 and 6, furnishing the desired products in good yield (85 94%).